Etika Tata Kelola: Analisis Bibliometrik VOSviewer dan Peluang Penelitian Masa Depan - Ekasari, Andini; Rahardja, Liana; Hidayat, Imam; Anwar, Juli (International Journal of Digital Entrepreneurship and Business, 2024)
This study aimed to conduct a bibliometric analysis to map Scopus-indexed scientific publications on Governance Ethics. The Publishing or Perish software collected Research data using the “governance ethic” keyword. This data was then processed using a VOS viewer to analyze and visualize the number of publications, researchers, keywords, and future research opportunities. The results revealed 499 scientific articles on governance and ethics, with the highest number published in 2021, totaling 42 articles. The earliest publication dates to 1982 by T. Purcell from Georgetown University, Washington, D.C., United States. The most prolific journal of publications is the Journal of Business Ethics, published by Springer Netherlands. Among researchers, Sison and Alejo Jose G. from Spain emerged as the most productive, with 8 publications and an H-index of 17. Sison is affiliated with the University of De Navarra, Pamplona, Spain. 926 authors were filtered down to 93, forming 10 networks and 2 clusters. Regarding keywords, 843 were filtered down to 138, with the most common being ethics, governance, business ethics, research ethics, and corporate social responsibility. The theoretical implication of this study lies in its utilization of bibliometric analysis for mapping governance ethics in Scopus-indexed scientific publications.